Dynamics of depositing and diffusion of drugs (chlorhexidine, 5-fluorouracil and doxorubicin) in hydrogel implants with different hydrogel crosslinking densities (Ukrainian Journal of Ophthalmology, 2025)
Background: Due to increasing prevalence of ocular trauma, more and more patients need to have their affected orbit, orbital adnexa, and periorbital area restored, which results in an increasing demand for implant materials. It is important for these materials to contain antimicrobial and antitumor drugs in order to prevent inflammation and recurrent inflammation around the implant before and after tumor removal.Purpose: To study the dynamics of depositing and diffusion of drugs (chlorhexidine, 5-fluorouracil and doxorubicin) in hydrogel implants with different hydrogel crosslinking densities.Material and Methods: Pharmaceuticals: 2.0% chlorhexidine digluconate; 5-fluorouracil (Ebewe Pharma, Unterach, Austria) infusion solution concentrate, 50 mg/ml; and doxorubicin (Ebewe), 2 mg/ml.Results: The time required for the drug concentration to reach the minimum therapeutic level was as small as several minutes for the low-density cross-linked hydrogel, whereas the diffusion lag time for the high-density cross-linked hydrogel was as large as several hours. The latter hydrogel was found to have a higher capacity for deposition of chlorhexidine digluconate and 5-fluorouracil, and is reasonable to be utilized in implants with a prolonged antibacterial effect, whereas the former hydrogel is reasonable to be utilized for a fast-release bolus antiseptic delivery. In in vitro experiments, the low-density cross-linked hydrogel hydrogel provided a 3-4-fold greater drug concentration in the environment, and allowed for a smoother and more prolonged drug release profile compared to the high-density cross-linked hydrogel hydrogel.Conclusion: Such a capacity for prolonged drug release will promote application of hybrid hydrogel implants for depositing anti-cancer drugs and maintaining effective concentrations of the latter at pathology focus.
Keywords: hybrid hydrogel; endoprosthesis; drug deposition and diffusion; degree of hydrogel crosslinking; reconstructive surgery